2017
DOI: 10.1186/s12937-017-0243-8
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inflammatory index and risk of first myocardial infarction; a prospective population-based study

Abstract: BackgroundChronic, low-grade inflammation is an established risk factor for cardiovascular disease. The inflammatory impact of diet can be reflected by concentrations of inflammatory markers in the bloodstream and the inflammatory potential of diet can be estimated by the dietary inflammatory index (DIITM), which has been associated with cardiovascular disease risk in some previous studies. We aimed to examine the association between the DII and the risk of first myocardial infarction (MI) in a population-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
92
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 94 publications
(97 citation statements)
references
References 50 publications
3
92
2
Order By: Relevance
“…In this same line of inquiry, the SU.VI.MAX study reported that a higher DI score was associated with higher diastolic and systolic blood pressure in adults (30–60 years) (Neufcourt et al, ). Another prospective population‐based study also indicated that men (though not women) with higher DII scores showed higher systolic blood pressure ( p = .005) (Bodén et al, ). Once again, age difference may contribute to the disparity in results between younger and older study cohorts.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In this same line of inquiry, the SU.VI.MAX study reported that a higher DI score was associated with higher diastolic and systolic blood pressure in adults (30–60 years) (Neufcourt et al, ). Another prospective population‐based study also indicated that men (though not women) with higher DII scores showed higher systolic blood pressure ( p = .005) (Bodén et al, ). Once again, age difference may contribute to the disparity in results between younger and older study cohorts.…”
Section: Discussionmentioning
confidence: 94%
“…The DII has been validated in previous studies with different measures of inflammation such as C‐reactive protein (CRP), IL‐6, and TNF‐α‐R2 (Shivappa et al, ; Wirth et al, ). Additionally, the DII has also been reported to be associated with several chronic inflammation‐related health outcomes such as cancer incidence and CVD (Bodén et al, ; Bondonno et al, ; Garcia‐Arellano et al, ; O'Neil et al, ; Ramallal et al, ; Zheng et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…However, these studies have reported inconsistent results for the relationship of anti‐inflammatory diet and CVD. Although a positive association of dietary inflammatory index (DII) and CVD was reported in several studies, no significant relationship was found in other investigations . In a systematic review and meta‐analysis study, it was reported that a high DII score appears to increase the risk of CVD by about 35% .…”
Section: Introductionmentioning
confidence: 94%
“…12 A Western dietary pattern rich in red meat, refined grains, butter, processed meat, high-fat dairy products, sweets, desserts, potatoes, eggs, hydrogenated fats, and sugared-sweetened beverages is known to increase levels of inflammatory markers; a Mediterranean dietary pattern rich in olive oil, nuts, fruits, vegetables, whole grains, and fish decreases these levels. 5,13 A high-fat diet may stimulate the activation of endothelial cells, enhancing the expression of adhesion molecules. A healthy diet is a rich source of antioxidants and fiber, and decreases the inflammatory responses.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, multiple studies demonstrated the positive link between adherence to proinflammatory diet (the higher DII score) and levels of serum glucose, as well as, the association between the DII score and serum levels of lipid profile [37][38][39][40]. Previous studies have shown that there is the association between the DII score and different chronic diseases such as obesity [41], metabolic syndrome (MetS) [42], cancers [35,[43][44][45], and CVDs [46][47][48]. In Iran, DII has been shown to be associated with various cancers [44,[49][50][51] and cataract [52] and specifically among Iranian women, a positive association has been observed between higher DII scores and spontaneous abortion [36], gestational diabetes mellitus [53] and decreased bone mineral density among postmenopausal women [54].…”
mentioning
confidence: 99%